Le cellule staminali: impiego clinico - Vandenbulcke, F.; Beltrame, G.; Vitale, N.D.; Di Matteo, B.; Kon, E. (Lo Scalpello - Journal, 2019)
THE CLINICAL APPLICATION OF MSCS IN ORTHOPAEDICS A systematic review of clinical applications of MSCs in the treatment of knee osteoarthritis (OA). Twenty-three papers were included in the final analysis (10 on BMAC and 13 on SVF). Of these, only 4 were randomised controlled trials (RCTs). The Coleman Score, used for bias risk evaluation, revealed an overall poor quality of the studies. In terms of clinical application, despite the apparent safety and the short-term positive clinical outcomes, clinicians reported different preparation and administration methods. The available literature is not sufficient to make any recommendation on the use of either product in clinical practice, even though they have both shown to be safe and have some short-term beneficial effects.